Knowledge, attitude, and associated factor towards cervical cancer prevention among primary and secondary school female teachers in Gondar town, North West Ethiopia, 2022 - Birtukan Atena Negash; Netsanet Habtie Bayu; Ashenafi Worku Woretaw (BMC, 2023)
Abstract Introduction Cervical cancer is uncontrolled proliferation of cells on the cervix. Worldwide, millions of women suffer from this disease. Cervical cancer can be prevented by increasing awareness and changing negative attitude about the cause and prevention of cervical cancer. The aim of this study was to identify the gap of knowledge, attitude and associated factor about cervical cancer prevention. Method Institution-based cross-sectional study was conducted to collect data from 633 female teachers who were working in primary and secondary schools in Gondar town by using a stratified sampling technique. The collected data were checked for any inconsistency, coded, and entered by using EPI INFO version 7 and analyzed by using SPSS version 25. Both Bivariable and multivariable logistic regression analysis was computed to identify the association between the dependent variable with independent variables. Variables having P-value < 0.05 were considered statistically significant. Result The response rate of this study was 96.4% (610). Of these 38.4% (95% CI; 34.49-42.23) and 56.2% (95% CI; 52.28-60.18) of teachers had good knowledge and positive attitude on cervical cancer prevention respectively. Factors affecting teachers knowledge level were studied language [AOR; 3.9; (1.509-10.122)], Natural Science [AOR 2.9;( 1.128-7.475)], being married [AOR: 0.386; [95% (0.188-0.792)], and heard information from health professionals [AOR; 0.53(0.311-0.925)]. Working in secondary school [AOR; 1.83(1.03-3.25)], have regular menstrual period [AOR; 2.32(1.49-3.62)], no history of abortion, (AOR; 0.45(0.23-0.89), and good knowledge status (AOR, 2.56(1.64-4.00) were significantly associated with positive attitude. Conclusion Most of teacher's knowledge and attitude regarding to cervical cancer prevention were poor. Being married, the field of study, and natural science, heard information from health professionals were factors associated with knowledge. Working in secondary school, having regular menstrual period, no history of abortion, and good knowledge were factors associated attitude regarding to cervical cancer prevention. Therefore, enhancing health promotion through mass media and established counseling program with reproductive health is important.